Increasing brain half-life of antibodies by additional binding to myelin oligodendrocyte glycoprotein, a CNS specific protein - Marie-Lynn Cuypers; Tom Jaspers; Jarne Clerckx; Simon Leekens; Christopher Cawthorne; Guy Bormans; Frederik Cleeren; Nick Geukens; Bart De Strooper; Maarten Dewilde (Fluids and Barriers of the CNS)
Abstract Background Therapeutic antibodies for the treatment of neurological disease show great potential, but their applications are rather limited due to limited brain exposure. The most well-studied approach to enhance brain influx of protein therapeutics, is receptor-mediated transcytosis (RMT) by targeting nutrient receptors to shuttle protein therapeutics over the blood–brain barrier (BBB) along with their endogenous cargos. While higher brain exposure is achieved with RMT, the timeframe is short due to rather fast brain clearance. Therefore, we aim to increase the brain half-life of antibodies by binding to myelin oligodendrocyte glycoprotein (MOG), a CNS specific protein. Methods Alpaca immunization with mouse/human MOG, and subsequent phage selections and screenings for MOG binding single variable domain antibodies (VHHs) were performed to find mouse/human cross-reactive VHHs. Their ability to increase the brain half-life of antibodies was evaluated in healthy wild-type mice by coupling two different MOG VHHs (low/high affinity) in a mono- and bivalent format to a β-secretase 1 (BACE1) inhibiting antibody or a control (anti-SARS-CoV-2) antibody, fused to an anti-transferrin receptor (TfR) VHH for active transport over the BBB. Brain pharmacokinetics and pharmacodynamics, CNS and peripheral biodistribution, and brain toxicity were evaluated after intravenous administration to balb/c mice. Results Additional binding to MOG increases the Cmax and brain half-life of antibodies that are actively shuttled over the BBB. Anti-SARS-CoV-2 antibodies coupled with an anti-TfR VHH and two low affinity anti-MOG VHHs could be detected in brain 49 days after a single intravenous injection, which is a major improvement compared to an anti-SARS-CoV-2 antibody fused to an anti-TfR VHH which cannot be detected in brain anymore one week post treatment. Additional MOG binding of antibodies does not affect peripheral biodistribution but alters brain distribution to white matter localization and less neuronal internalization. Conclusions We have discovered mouse/human/cynomolgus cross-reactive anti-MOG VHHs which have the ability to drastically increase brain exposure of antibodies. Combining MOG and TfR binding leads to distinct PK, biodistribution, and brain exposure, differentiating it from the highly investigated TfR-shuttling. It is the first time such long brain antibody exposure has been demonstrated after one single dose. This new approach of adding a binding moiety for brain specific targets to RMT shuttling antibodies is a huge advancement for the field and paves the way for further research into brain half-life extension.